Evidence of In Vivo Prophage Induction during Clostridium difficile Infection - Meessen-Pinard, Mathieu (American Society for Microbiology, 2012)
Prophages contribute to the evolution and virulence of most bacterial pathogens, but their role in Clostridium difficile is unclear. Here we describe the isolation of four Myoviridae phages, ϕMMP01, ϕMMP02, ϕMMP03, and ϕMMP04, that were recovered as free viral particles in the filter-sterilized stool supernatants of patients suffering from C. difficile infection (CDI). Furthermore, identical prophages were found in the chromosomes of C. difficile isolated from the corresponding fecal samples. We therefore provide, for the first time, evidence of in vivo prophage induction during CDI. We completely sequenced the genomes of ϕMMP02 and ϕMMP04, and bioinformatics analyses did not reveal the presence of virulence factors but underlined the unique character of ϕMMP04. We also studied the mobility of ϕMMP02 and ϕMMP04 prophages in vitro. Both prophages were spontaneously induced, with 4 to 5 log PFU/ml detected in the culture supernatants of the corresponding lysogens. When lysogens were grown in the presence of subinhibitory concentrations of ciprofloxacin, moxifloxacin, levofloxacin, or mitomycin C, the phage titers further increased, reaching 8 to 9 log PFU/ml in the case of ϕMMP04. In summary, our study highlights the extensive genetic diversity and mobility of C. difficile prophages. Moreover, antibiotics known to represent risk factors for CDI, such as quinolones, can stimulate prophage mobility in vitro and probably in vivo as well, which underscores their potential impact on phage-mediated horizontal gene transfer events and the evolution of C. difficile.